Functionalization of silk with actinomycins from Streptomyces anulatus BV365 for biomedical applications - Ilic-Tomic, Tatjana; Kramar, Ana; Kostic, Mirjana; Vojnovic, Sandra; Milovanovic, Jelena; Petkovic, Milos; D’Agostino, Paul M.; Gulder, Tobias A. M.; Nikodinovic-Runic, Jasmina (Frontiers in Bioengineering and Biotechnology, 2024)
Silk, traditionally acclaimed as the “queen of fiber,” has been widely used thanks to its brilliant performance such as gentleness, smoothness and comfortableness. Owing to its mechanical characteristics and biocompatibility silk has a definitive role in biomedical applications, both as fibroin and fabric. In this work, the simultaneous dyeing and functionalization of silk fabric with pigments from Streptomyces anulatus BV365 were investigated. This strain produced high amounts of orange extracellular pigments on mannitol-soy flour agar, identified as actinomycin D, C2 and C3. The application of purified actinomycins in the dyeing of multifiber fabric was assessed. Actinomycins exhibited a high affinity towards protein fibers (silk and wool), but washing durability was maintained only with silk. Acidic condition (pH5) and high temperature (65°C) facilitated the silk dyeing. The morphologies and chemical components of the treated silk fabrics were analyzed using scanning electron microscopy and Fourier transform infrared spectroscopy. The results showed the pigments bind to the silk through interaction with the carbonyl group in silk fibroin rendering the functionalized, yet surface that does not cause skin irritation. The treated silk exhibited a remarkable antibacterial effect, while the biocompatibility test performed with 3D-reconstructed human epidermis model indicated safe biological properties, paving the way for future application of this material in medicine.